Solar Divergence Collimators for Optical Characterisation of Solar Components - D. Fontani; P. Sansoni; E. Sani; S. Coraggia; D. Jafrancesco; L. Mercatelli (International Journal of Photoenergy)
Experimentation and laboratory optical tests on solar components are central aspects of the research on renewable energies. The key element of the proposed testing systems is a solar divergence collimator, which exactly reproduces in laboratory the sunlight divergence, while commercial solar simulators are mainly aimed to replicate intensity and spectrum of the sun. Precise solar divergence reproduction is essential to correctly assess the optical properties and to simulate the operative conditions of a solar collecting device. Optical characterisation and experimentation can give information about production quality and homogeneity; moreover, specific tests can address the serial production of solar components detecting defects type and location. For Concentrating Photovoltaic systems, appropriate tests can analyze solar concentrators of various shapes, dimensions, and collection features. Typically, to characterise a solar component the most important and commonly examined quantities are collection efficiency, image plane analysis, and angle dependence.